EFEKTIVITAS MODEL MNEMONIC UNTUK MENINGKATKAN KETERAMPILAN MENARI PADA TARI INDONESIA MENARI DI EKSTRAKURIKULER SENI TARI MAN 1 LAMPUNG TENGAH - Umi Khoirul Latifah; Amelia; Lora Gustia Ningsih (STKIP Subang, 2026)
This study aims to examine the effectiveness of a mnemonic model in improving students’ dance skills in Indonesian Dance during the extracurricular program at MAN 1 Lampung Tengah. The study employed a quantitative approach using a one-group pretest–posttest design. The research sample consisted of 32 students who actively participated in the dance extracurricular activity. Data were collected through classroom observations, dance performance tests, and assessment instruments evaluated by the teacher to measure students’ mastery of Indonesian dance movements before and after the implementation of the mnemonic model. The findings revealed a significant improvement in students’ mastery of dance movements following the treatment. Statistical analysis showed a significance value of 0.000, which was lower than 0.05, indicating that H₀ was rejected and H₁ was accepted. These results demonstrate a significant difference between students’ abilities before and after the intervention. The mean score increased from 1.73 in the pretest to 3.39 in the posttest, reflecting substantial progress in learning outcomes. The improvement suggests that the mnemonic model effectively supports students in remembering, understanding, and performing dance movements more accurately. Furthermore, the enhancement of dance skills was observed across the aspects of wiraga (movement), wirama (rhythm), and wirasa (expression). Therefore, the mnemonic model can be considered an effective learning strategy for developing students’ psychomotor abilities and improving dance performance in extracurricular dance education.